Pengaruh Firm Size, Leverage, Dan Profitability Terhadap Earnings Response Coefficient : Studi Kasus Pada Perusahaan Sektor Pertambangan Yang Terdaftar Di BEI Tahun 2020-2022 - Nabila Zaina Aiffa; Isyfa Fuhrotun Nadhifah (Universitas Kristen Indonesia Toraja, 2024)
This research aims to determine the influence of firm size, leverage and profitability on the Earnings Response Coefficient. Earnings Response Coefficient (ERC) or earnings response coefficient is a quantity that shows the relationship between profits and share prices. Research on ERC is developing quickly and is interesting to observe because ERC is useful for investors as a research model to determine the market reaction to information on a company's earnings, so that it can be seen how likely the stock price will respond to information on the company's earnings. The data used in this research is secondary data, namely in the form of financial reports of mining companies listed on the Indonesia Stock Exchange (BEI) during 2020-2022 which are accessed via www.idx.co.id and each company's website as well as daily share price data. which is accessed via Yahoo Finance. The population in this research is mining sector companies listed on the Indonesia Stock Exchange (BEI) during the 2020-2022 period. The analytical tool used is multiple linear regression analysis with the SPSS 25 program. The results of hypothesis testing show that firm size has a positive and significant effect on the earnings response coefficient, leverage has no significant effect on the earnings response coefficient, and profitability has a positive and significant effect on the earnings response coefficient.